The Contribution of Muhammadiyah Students in Realizing Indonesia Emas 2045: A Communication Analysis of Khittah.co Media Coverage on the IPM Movement in South Sulawesi - Kamsar; Hadisaputra; Andi Asywid Nur (Indonesian Journal Publisher, 2026)
Amid the strengthening agenda of Indonesia Emas 2045, students are no longer positioned merely as objects of development but as strategic actors who actively contribute to shaping the nation’s future. This study aims to analyze the contribution of Muhammadiyah students in realizing Indonesia Emas 2045 through media coverage on Khittah.co regarding the movement of the Muhammadiyah Student Association (IPM) in South Sulawesi. This research employs a descriptive qualitative approach. The data are derived from news articles on Khittah.co that report on the activities of IPM South Sulawesi at various leadership levels, including regional, district, and branch levels, collected through documentation techniques. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing using Pierre Bourdieu’s Capital Theory as an analytical framework. The results show that the contributions of Muhammadiyah students in the IPM South Sulawesi movement are represented through four main narratives: educational transformation, social solidarity and humanitarianism, strengthening youth leadership, and ecological awareness. These four narratives reflect the accumulation of cultural capital, social capital, and symbolic capital developed by IPM South Sulawesi in building human resources from an early age. This contribution affirms the role of IPM South Sulawesi as a strategic actor in supporting the realization of an inclusive and sustainable Indonesia Emas 2045, not only through strengthening intellectual capacity but also through the formation of character, social ethics, and environmental awareness.